Characteristic of Posterior Capsular Opacification (PCO) in Dr. Mohammad Hoesin General Hospital: A Retrospective Study - Gina Sonia Fensilia Yolanda; Allie Solahuddin (Sriwijaya Journal of Ophthalmology, 2022)
Introduction: Posterior Capsular Opacity (PCO), also called "secondary cataract," is the most common complication after cataract surgery and occurs in 20-50% of patients within 2 – 5 after cataract surgery before. The current therapeutic option for PCO is using capsulotomy laser Nd:YAG (Neodymium: Yttriume-Auminume-Garnet) to break up opacities in the central or visual axis of the posterior capsule. Methods: This retrospective study was conducted in June 2022 with all patients in Lens Subdivision who were diagnosed with PCO in outpatient poly Dr. Mohammad Hoesin General Hospital Palembang from October 2021 – March 2022. Total sampling was obtained from the medical record of the patient. Each patient had previous cataract surgery with a range of 1 – 7 years before. Results: There are 15 samples in this study, with a total of 7 women (46.7%) and 8 men (53.3%). The mean age is 62.5 years, with the youngest age 14 years old and the oldest 73 years old. Seven patients (46.7%) are the most surgical history in the 3rd to 5th year. Each sample diagnosed with PCO was subjected to the Nd:YAG laser procedure with visual acuity before the procedure ranging from 1/~ to 6/15, and the best vision after the Nd:YAG laser procedure reached 6/6 vision. Conclusion: PCO commonly occurs after cataract surgery & occurred within 2 -5 years after cataract surgery. Therapeutic management can be using the Nd:YAG laser capsulotomy technique and surgical techniques to maintain visual function after cataract surgery.